2021
DOI: 10.1002/mnfr.202000869
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant‐like Effects of Degraded Porphyran Isolated fromPorphyra haitanensis

Abstract: Introduction Degraded porphyran is a bioactive polysaccharide extracted from Porphyra haitanensis (P. haitanensis). According to the previous studies, it produced anti‐inflammatory activity, but little is known about its effects on depression. Methods and Results As inflammation is one of the critical factors involved in the development of depression, this study aims to elucidate the potential antidepressant‐like effects of degraded porphyran. The results show that acute porphyran treatment decreased the immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…30 Immobility time in FST and TST reflects a state of desperation, which is similar to the symptom of depressed patients, and the two behavioral tests are widely used to initial screening of an antidepressant. 31 In this study, we measured the body weight of mice and conducted three classic behavioral tests, SPT, FST, and TST, to explore the effect of L. plantarum R6-3 on CUMS-induced depressive mice. In this study, the body weights of the mice showed an increasing trend during eight weeks and there was no significant difference between each group in the first two weeks ( p > 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Immobility time in FST and TST reflects a state of desperation, which is similar to the symptom of depressed patients, and the two behavioral tests are widely used to initial screening of an antidepressant. 31 In this study, we measured the body weight of mice and conducted three classic behavioral tests, SPT, FST, and TST, to explore the effect of L. plantarum R6-3 on CUMS-induced depressive mice. In this study, the body weights of the mice showed an increasing trend during eight weeks and there was no significant difference between each group in the first two weeks ( p > 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the enhanced activity of the BDNF/TrkB/ERK/CREB signaling pathway is critical for neuronal survival, neural protrusion growth and branching. 31 A systematic review of clinical studies has shown that BDNF is directly involved in the pathophysiology of depression and the recovery of BDNF function may be the basis for antidepressant drug treatment. 40 BDNF plays a role through its high-affinity receptor tyrosine protein kinase B (TrkB), and BDNF and its receptor TrkB are widely and abundantly expressed in the central nervous system, activating various intracellular signaling pathways related to neuroprotection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the maturation of IL-1β needs to go through the following two stages (Ismael et al, 2021): The first stage is that the MSU crystal acts on cell surface TLRs to activate NF-κB, which causes IL-1β and NLRP3 gene transcription and subsequently generates inactive IL-1β precursors. In the second stage, NLRP3 inflammasome, which is activated by the MSU crystal via different pathways, will activate caspase-1 and, thus, cleave IL-1β precursors into mature IL-1β (Kelley et al, 2019;Yi et al, 2021). If there is only the activated TLRs signaling pathway but not the activation of NLRP3, the precursor IL-1β cannot exert any biological activity.…”
Section: Discussionmentioning
confidence: 99%